Didi-Huberman and the image - Larsson, Chari (Book collections on Project MUSE., 2020)
Philosopher and art historian Georges Didi-Huberman is one of the most innovative and influential critical thinkers writing today. This book is the first English-language study of his writing on images. An image is a form of representation, but what are the philosophical frameworks supporting it? The book considers how Didi-Huberman takes up this question repeatedly over the course of his career. Placing his project in relation to major historical and intellectual contexts, it shows not only how he modifies dominant disciplinary traditions, but also how the study of images is central to a new way of thinking about poststructuralist-inspired art history.